Pendidikan Kesehatan dan Physical Exercise sebagai Upaya Menurunkan Tingkat Kelelahan dan Stress Warga Kampus International Islamic University Malaysia - Chayati, Nur; Agung Rejecky; Puspitowarno; Aqila Fadiya Hayati Rusydi; Thandar Soe Sumaiyah Jamaludin (Edujavare Publishing, 2023)
Based on the results of a survey on the level of fatigue and stres of IIUM students, it is known that 30% felt mild fatigue and 70% felt moderate fatigue. For stres levels, it was found that 40% experienced moderate stres, 30% experienced mild stres. This condition is not recognized and if it continues, it will reduce the health status of IIUM Malaysia campus residents, so efforts are needed to improve their health status. The aim of this service research is to increase knowledge about stres and work fatigue, reduce fatigue levels and reduce stres levels for IIUM campus residents. The method applied in this community service is Community Based Research (CBR) using the Forum Group Discussion (FGD) approach. Community service activities that have been carried out include providing health education about the impact of work on fatigue and stres, followed by light physical exercise. There were 36 participants who attended. The results of the service carried out with a pre-testt and post-testt, knowledge about fatigue and stres, almost all participants experienced a significant increase. The average pre-testt and post-testt fatigue level score was 47.77, increasing to 94.72. For knowledge about stres, the average pre-testt and post-testt scores were 49.72 to 96.11. This community service shows that implementing formal education in the classroom carries the risk of causing serious health problems, so students and other campus residents are given informal education content in the form of relaxing activities outside the classroom.